Analisis kinerja keuangan pengelolaan alokasi dana desa berdasarkan rasio efektivitas dan rasio pertumbuhan pada Desa Sribunga - Indiskayani, Indiskayani; Nengsih, Titin Agustin; Dessy, Anggraini (e-Journal Perdagangan Industri dan Moneter, 2024)
This research aims to find out how financial performance is in managing village fund allocation in Sribunga Village, Buay Pemuka Bangsa Raja District, East Ogan Komering Ulu Regency in 2019-2022 by looking at the effectiveness ratio and growth ratio. The type of research used is quantitative descriptive research where researchers use data obtained from financial reports on village fund allocations in the 2019-2022 village income and expenditure budget. Furthermore, the data analysis technique used uses the effectiveness ratio and growth ratio formulas. The research results show that the financial performance of the Sribunga Village government, East OKU Regency is good in managing village funds. This can be seen from the effectiveness value obtained on average of 99.52%. The growth ratio has a fluctuating value, where in 2021 the value increased by 29.68%, while the growth ratio for village fund expenditure increased by 30.81 in 2021. In 2020 and 2022 there was a decrease in the income growth ratio and expenditure growth ratio.